Responses to direct-to-consumer advertising in Australia: Comparing experience. Issue 4 (2nd October 2022) - Goodall, Stephen; Viney, Rosalie; Street, Deborah; Waller, David S.; Zhao, Fei Li
Absract: This paper examines the potential effect of Direct-to-Consumer (DTC) advertising on consumers' behavioral intentions in relation to a medical issue. Using an online experiment, 1295 people were randomized to two information conditions. One group watched an advertisement for a hypothetical cold sore medicine, while a second (control) group did not view the advertisement, before both groups answered questions on symptoms. The responses were analyzed based on group allocation and the respondents' experience with cold sores. Results indicate that those who viewed the advertisement were more likely to choose the product, and the advertisement had larger effects based on consumer experience.